The problem of underflooding the objects of economy as a source of hydrogenic emergencies - Arefyeva, Елена Валентиновна; Mirmovich, Эдуард Григорьевич (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
The authors give the review of social and economic damage as the consequence of ground water raising. The article considers one of the main causes of underflooding – the man-made one.